2020
DOI: 10.1007/s10989-020-10094-8
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Artificial Neural Network Approaches to Modeling and Optimization of Fermentation Conditions for Production of a Surface/Bioactive Glyco-lipo-peptide

Abstract: A freshwater alkaliphilic strain of Pseudomonas aeruginosa, grown on waste frying oil-basal medium, produced a surface-active metabolite identified as glycolipopeptide. Bioprocess conditions namely temperature, pH, agitation and duration were comparatively modeled using statistical and artificial neural network (ANN) methods to predict and optimize product yield using the matrix of a central composite rotatable design (CCRD). Response surface methodology (RSM) was the statistical approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…To select most suitable inoculum size (spore density) for the fermentation, inoculum sizes were screened by the OFAT approach by inoculating 3% (v/v) spore suspension of different inoculum sizes ranging from 10 3 to 10 9 spore-forming units per milliliter (sfu/mL) into minimal medium containing selected extraneous carbon and nitrogen substrates. Working spore concentrations were prepared by the spectrophotometric method as described in Ekpenyong et al ( 2020a ) and experimental set up, incubations, harvest, determinations of enzyme activity and statistical analyses were as described under carbon screening section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To select most suitable inoculum size (spore density) for the fermentation, inoculum sizes were screened by the OFAT approach by inoculating 3% (v/v) spore suspension of different inoculum sizes ranging from 10 3 to 10 9 spore-forming units per milliliter (sfu/mL) into minimal medium containing selected extraneous carbon and nitrogen substrates. Working spore concentrations were prepared by the spectrophotometric method as described in Ekpenyong et al ( 2020a ) and experimental set up, incubations, harvest, determinations of enzyme activity and statistical analyses were as described under carbon screening section.…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme dosages were two-fold dilutions from enzyme stock solution ranging from 1.148 to 1174.898 µg/mL. Mycoplasma sterility tests, viability and subsequent cytotoxicity studies using the sulforhodamine B (SRB) assay were as described in Asitok and Ekpenyong ( 2019 ) and Ekpenyong et al ( 2020a ). Experiments were conducted in triplicates and results, expressed as % cell viability, were presented as means of triplicate determinations.…”
Section: In-vitro Anti-cancer Activities Of Aspergillus Canmentioning
confidence: 99%
“…Like every other value-added microbial product, the natural or baseline yield is usually low and costeffectiveness very poor (Ekpenyong et al 2021a). To improve production economics, biosynthesis of one or more value-added metabolite during bioconversion of agro-industrial waste on a large scale has been suggested (Ekpenyong et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…To improve production economics, biosynthesis of one or more value-added metabolite during bioconversion of agro-industrial waste on a large scale has been suggested (Ekpenyong et al 2017a). To improve yield and/or activity, a number of nutritional and environmental requirements of high-yielding microbial strains need to be optimized (Ekpenyong et al 2017a, b;2021a). Response surface methodology (RSM) and artificial neural network (ANN) methods have become gold standards for bioprocess optimizations for the dual purposes of improving yield and cost-effectiveness (Kanno et al 2020;Ekpenyong et al 2021a;Dwibedi et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation